Developmental mediation of genetic variation in response to the Fast Track prevention program. (2nd February 2015) - Belsky, Jay; van IJzendoorn, Marinus H.; Albert, Dustin; Belsky, Daniel W.; Crowley, D. Max; Bates, John E.; Pettit, Gregory S.; Lansford, Jennifer E.; Dick, Danielle; Dodge, Kenneth A.
Abstract We conducted a developmental analysis of genetic moderation of the effect of the Fast Track intervention on adult externalizing psychopathology. The Fast Track intervention enrolled 891 children at high risk to develop externalizing behavior problems when they were in kindergarten. Half of the enrolled children were randomly assigned to receive 10 years of treatment, with a range of services and resources provided to the children and their families, and the other half to usual care (controls). We previously showed that the effect of the Fast Track intervention on participants' risk of externalizing psychopathology at age 25 years was moderated by a variant in the glucocorticoid receptor gene. Children who carried copies of the A allele of the single nucleotide polymorphism rs10482672 had the highest risk of externalizing psychopathology if they were in the control arm of the trial and the lowest risk of externalizing psychopathology if they were in the treatment arm. In this study, we test a developmental hypothesis about the origins of this for better and for worse Gene × Intervention interaction (G × I): that the observed G × I effect on adult psychopathology is mediated by the proximal impact of intervention on childhood externalizing problems and adolescent substance use and delinquency. We analyzed longitudinal data tracking the 270 European American children in the Fast Track randomized control trial with available genetic information (129 intervention children, 141 control group peers, 69% male) from kindergarten through age 25 years. Results show that the same pattern of for better and for worse susceptibility to intervention observed at the age 25 follow-up was evident already during childhood. At the elementary school follow-ups and at the middle/high school follow-ups, rs10482672 predicted better adjustment among children receiving the Fast Track intervention and worse adjustment among children in the control condition. In turn, these proximal G × I effects early in development mediated the ultimate G × I effect on externalizing psychopathology at age 25 years. We discuss the contribution of these findings to the growing literature on genetic susceptibility to environmental intervention.